2018
DOI: 10.1080/15548627.2018.1505155
|View full text |Cite
|
Sign up to set email alerts
|

Galectins control MTOR and AMPK in response to lysosomal damage to induce autophagy

Abstract: The Ser/Thr protein kinase MTOR (mechanistic target of rapamycin kinase) regulates cellular metabolism and controls macroautophagy/autophagy. Autophagy has both metabolic and quality control functions, including recycling nutrients at times of starvation and removing dysfunctional intracellular organelles. Lysosomal damage is one of the strongest inducers of autophagy, and yet mechanisms of its activation in response to lysosomal membrane damage are not fully understood. Our recent study has uncovered a new si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 1 publication
3
80
0
Order By: Relevance
“…Our study was identical to the opinion that DIRAS3 was correlated with poor prognosis of GBM and was a risk factor for GBM survival. As a member of lectin family, LGALS8 (galectin‐8) plays key roles in various cellular processes, such as autophagy, cytoskeletal rearrangement, immunity and inflammation, as well as tumour progression . LGALS8 can recognize lysosome damage and promote autophagy through inhibiting mTOR activity .…”
Section: Discussionmentioning
confidence: 99%
“…Our study was identical to the opinion that DIRAS3 was correlated with poor prognosis of GBM and was a risk factor for GBM survival. As a member of lectin family, LGALS8 (galectin‐8) plays key roles in various cellular processes, such as autophagy, cytoskeletal rearrangement, immunity and inflammation, as well as tumour progression . LGALS8 can recognize lysosome damage and promote autophagy through inhibiting mTOR activity .…”
Section: Discussionmentioning
confidence: 99%
“…4c, d). It is well-known that the degradation of the phospho-mTOR could induce autophagy [29]. All the above results indicated that YAP knock-down could induce autophagy by inhibiting activation of Akt/mTOR signaling pathway.…”
Section: Yap Induces Activation Of Akt/mtor Signaling Pathway Via Supmentioning
confidence: 77%
“…A partial explanation for this observation might be that Gal3 initially promotes interactions between ALIX and the downstream ESCRT-III effector CHMP4. At later times, however, Gal3 controls the autophagic response via TRIM16 supported by Gal8/9 that regulate mTOR/AMPK [ 133 ]. A very recent study showed that macrophages challenged with either invasive bacteria or LLOMe activates the Parkinson’s disease related kinase leucine-rich repeat kinase 2 (LRKK2), which in turn recruits the Rab GTPase Rab8A.…”
Section: Membrane Damage Recognition and Cell Responsementioning
confidence: 99%
“…The interplay of Gal3/8/9 with the ESCRT machinery, autophagy and metabolic signaling is also observed during membrane damage upon M. tuberculosis and Coxiella burnetii infection [ 129 , 133 ]. Interestingly, mycobacterial effectors EsxG/TB9.8 and EsxH/TB10.4 secreted by the ESX-3 T7SS secretion system antagonize the ESCRT response with a kinetic that matches the speed with which the cell responds, showing that bacteria have also developed efficient countermeasures against membrane repair mechanisms [ 135 ].…”
Section: Membrane Damage Recognition and Cell Responsementioning
confidence: 99%